La « Philosophie spontanée d'un savant » - Fabienne Toupin (Anglophonia)
Henri Adamczewski developed an utterer-centered approach to the grammar of English for which he is well-known in France. Contrary to other linguists, he never gave an account of his philosophy of language, and in this paper I hypothesize that this philosophy, which remained throughout mostly unconscious, mixes materialist and idealistic elements.This paper aims at making explicit Adamczewski's philosophy of language, a condition for a deeper understanding of the linguist's views and a better assessment of his role in the recent history of English linguistics. I will try to demonstrate that the way Adamczewski's philosophical background influences his theoretical views is of special interest. As I go along I will compare the philosophical principles brought to light with those of the philosophy of language prevailing in Adamczewski's time, and in that respect this paper can also be seen as a critical study of a particular philosophical system.